The Development of the credit system in Russia: the Needs and Preferences of the Population - Дениc Олегович Стребков; Ольга Борисовна Грибанова (Journal of Economic Sociology, 2010)
The credit system has been developing very actively during the last 2-3 years in Russia. However only a few Russians have the experience of getting a consumer credit from the state or a private bank. The object of the study is the adult population of 18 years and more living in the big cities in Russia. The subject of the research is the people preferences toward the debt and credit behavior of the population. The goal of the study is to analyze the current credit behavior in order to identify main preferences toward debt and to estimate the perspectives for future development of the credit system in Russia. The data source is the flat questionnaire of households collected in 2002 in 5 Russian key big cities: Moscow, Samara, Yekaterinburg, Krasnodar and Pskov.